The Case Study of Nesfatin-1 in the Pancreas of Tursiops truncatus - Gatta, Claudia; De Felice, Elena; D’Angelo, Livia; Maruccio, Lucianna; Leggieri, Adele; Lucini, Carla; Palladino, Antonio; Paolucci, Marina; Scocco, Paola; Varricchio, Ettore; de Girolamo, Paolo (Frontiers in Physiology, 2018)
Nesfatin-1(Nesf-1) is an anorexigenic peptide involved in the regulation of homeostatic feeding. Nesf-1 is expressed in the central nervous system and other organs, including pancreas, where it promotes the release of insulin from β-cells. This raises the possibility that Nesf-1dysfunction could be involved in metabolic disorders, particularly in type 2 diabetes mellitus (T2D). Recently, it has been discovered that dolphins can be a natural animal model that fully replicates human T2D, due to its prolonged glucose tolerance curve and maintanaince of a state of hyperglycemia similar to human T2D during fasting. This correspondence suggests that dolphins may be a suitable model for investigating physiological and pathological metabolic disorders. Here, we have characterized Nesf-1 distribution in the pancreas of the common bottlenose dolphin (Tursiops truncatus) and measured plasmatic levels of Nesf-1 and glucose during fasting and post-prandial states. The Mediterranean marine mammal tissue bank (MMMTB) of the University of Padova provided us with pancreas samples, derived from four animals, and plasma samples, collected before and after the main meal. Interestingly, our results showed that Nesf-1-immunoreactive cells were distributed in Langerhans islets, co-localized with glucagon in α-cells. Similar to humans, dolphin plasma Nesf-1 concentration doesn’t show a statistically significant difference when comparing fasting and post-prandial states. On the other hand, blood glucose levels were significantly higher before than after the main meal. Our data provide a comparative analysis for further studies on the involvement of Nesf-1 in mammalian metabolic disorders.